2001
DOI: 10.1046/j.1523-1755.2001.060003957.x
|View full text |Cite
|
Sign up to set email alerts
|

Podocyte depletion and glomerulosclerosis have a direct relationship in the PAN-treated rat

Abstract: This report supports the growing body of data linking glomerulosclerosis directly to a reduction in relative podocyte number [increased glomerular area per podocyte (GAPP)]. It raises important questions related to the mechanisms of podocyte loss, strategies for prevention of podocyte depletion, and the prevention of progression of glomerular diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
290
1
3

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 356 publications
(307 citation statements)
references
References 33 publications
13
290
1
3
Order By: Relevance
“…Recent observations in humans describe a striking relationship between podocyte depletion and progression to end-stage renal disease in types 1 and 2 diabetic glomerulosclerosis and in IgA nephropathy (20 -24). These reports are based in turn on an extensive body of literature in experimental animals that provides a strong experimental underpinning for this conclusion (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). These experimental studies are well supported by a long-standing clinical literature describing a correlation between glomerulosclerosis and podocyte injury (1).…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Recent observations in humans describe a striking relationship between podocyte depletion and progression to end-stage renal disease in types 1 and 2 diabetic glomerulosclerosis and in IgA nephropathy (20 -24). These reports are based in turn on an extensive body of literature in experimental animals that provides a strong experimental underpinning for this conclusion (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). These experimental studies are well supported by a long-standing clinical literature describing a correlation between glomerulosclerosis and podocyte injury (1).…”
Section: Discussionmentioning
confidence: 83%
“…We previously used a method for estimating podocyte number that examined only midglomerular profiles and that did not correct podocyte nuclear counts for double counting and where we assumed the section thickness to be 3 m (19). By means of this approach, we defined a value for glomerular area per podocyte of 1500 to 1600 m 2 to be the approximate threshold above which glomerulosclerosis would be expected to occur.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing evidence suggests that the podocyte is the culprit in the great majority of glomerular diseases because loss of podocytes beyond a certain threshold induces glomerulosclerosis [1-4]. For example, podocyte numbers are reduced in proportion to the severity of injury and the magnitude of proteinuria is related to the extent of reduced podocyte number.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing experimental and clinical evidence has demonstrated that the podocyte number is a critical determinant in the development of glomerulosclerosis (1), and podocytopenia may lead to massive proteinuria and ultimate renal scarring (2). The causes of podocytopenia include apoptosis, detachment, and inability or lack of podocytes to proliferate (3).…”
Section: Introductionmentioning
confidence: 99%